Novel method and its mechanism of reconstruction of commercial alumina to homogeneous porous alumina composite material. Issue 16 (November 2019) - Gao, Shuaibo; Wang, Shuai; Kong, Jian; Xu, Ning; Xing, Pengfei
Abstract: In this study, a novel method for reconstruction of commercial alumina to a homogeneous porous alumina composite material (HPACM) using an alumina powder, boric acid, and Na2 SO4 and Na2 CO3 additives is proposed for the first time and experimentally evaluated in detail. The properties of the as-prepared porous materials and their formation mechanisms are investigated. Unlike the traditional complex methods for manufacturing of porous alumina including electrochemical anodisation of aluminium and chemical etching, the HPACM can be simply prepared through sintering and dissolution. Scanning electron microscopy and N2 adsorption–desorption isotherm analyses demonstrate the formation of the HPACM with a diameter distribution centred at ∼20 nm after the sintering and decomposition at high temperatures and dissolution at room temperature. Transmission electron microscopy and X-ray diffraction results show that the main components of the as-prepared HPACM are alumina and sodium aluminate. The formation of the HPACM is attributed mainly to the reactions between the alumina powder, boric acid, and Na2 SO4 and Na2 CO3 additives at high temperatures and dissolution of the intermediate product of sodium aluminate at room temperature. A NaCl additive does not contribute to the formation of the intermediate product during the sintering process, owing to its considerable vapour loss at low temperatures. Moreover, a nanoindentation test shows that the HPACM has a good mechanical strength.